Student Perceptions of Their Interactions with Peers at a Cyber Charter High School - Borup, Jered; Walters, Shea; Call-Cummings, Megan (Online Learning, 2020)
K-12 online students are increasingly communicating and collaborating with their peers; however, research on the topic is limited—especially research examining students’ perceptions and experiences. Guided by the Adolescent Community of Engagement framework’s concept of peer engagement, this case study examined learner-learner interactions at a cyber charter high school. Ten students were selected by teachers based on their ability to independently engage in learning activities—five students were more independent and five required more support from others. Each student took part in two, hour-long interviews for a total of 20 interviews. The interviewers covered students’ perceptions an experiences regarding teachers, parents, and peers. This report only focuses on peers. Students found that their interactions with peers allowed them to develop friendships, improve their motivation, receive peer instruction, and collaborate effectively with others. Challenges are also covered. The article concludes with recommendations for research and practice.